THE ROLE OF ICT IN CREATING INTERACTIVE LEARNING AND FOSTERING STUDENT CREATIVITY: A LITERATURE REVIEW - Imam Zaky Mubarok; Sillia Iriana (Al-Irsyad: Journal of Education Science, 2025)
The use of interactive learning media has emerged as an innovative solution to enhance the quality of education, particularly in the digital era. Educational institutions need to optimize the use of learning media. This study aims to explore the functions and roles of Information and Communication Technology (ICT) in creating interactive learning environments, fostering student creativity, and improving teachers' knowledge of technology utilization. The research was conducted using a literature review method, which involves analyzing and synthesizing information from various carefully selected sources through several stages: (a) formulating the initial question, (b) conducting a scoping search, (c) mapping the literature, and (d) identifying keyword criteria. The findings indicate that interactive learning media can improve material comprehension, learning motivation, and active student engagement in the learning process. Through the integration of technology, such as projectors and educational videos, students can learn in a more dynamic and engaging manner, thereby developing their social skills and critical thinking abilities. The implementation of ICT is highly influenced by teachers' capabilities in understanding technological knowledge, pedagogy, and content mastery. The main challenges include limited technological infrastructure and insufficient teacher competency, while supporting factors encompass the provision of hardware, regular training, and school policies that encourage ICT utilization.